The Organizational learning and its role in building the Entrepreneurship abilities Exploratory research in Zain Communications Company - Karbala Branch - ali abd alamir abd alhussein kmona (Iraqi Journal for Administrative Sciences, 2024)
The research topic tackled the organizational learning and its role in building the Entrepreneurship abilities, The research sought to achieve several of the most important goals (Know the importance of organizational learning and Entrepreneurship abilities for this company as vital variables important for the life of all sectors and organizations, including the communications sector, And to reveal the level of correlation and influence between organizational learning and Entrepreneurship abilities in the surveyed company) . Due to the importance of the communications sector and its role in the service of society and organizations, the research was carried out in (Zain Communications Company - Karbala Branch), The research was conducted on the sample of (70) of the employees who occupied many positions within the administrative staff In the surveyed company . The research was based on the questionnaire to obtain data and information. For the purpose of processing this information, researchers used a variety of statistical methods (Alpha Cronbach test, weighted mean, standard deviation, variance coefficient, response strength, correlation coefficient, simple linear regression, Interpretation coefficient R2 , F test, and T test) . The research ended with a set of conclusions, most notably (The surveyed company's interest in all variables as well as the sub-dimensions of the research, The existence of associative and affective relations between all search variables and their sub-dimensions), The research also found several recommendations, most notably (The importance of adopting the Entrepreneurship philosophy in the surveyed company, which is investigated by knowing the priorities of competition and how to build it and improve the level of employees through the work of educational seminars on the concept of leadership abilities and to follow the highest response to adapt to the changes internal and external environment) .